Impact of short-chain galactooligosaccharides on the gut microbiome of lactose-intolerant individuals - Azcarate-Peril, M. Andrea; Ritter, Andrew J.; Savaiano, Dennis; Monteagudo-Mera, Andrea; Anderson, Carlton; Magness, Scott T.; Klaenhammer, Todd R. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Directed modulation of the colonic bacteria to metabolize lactose effectively is a potentially useful approach to improve lactose digestion and tolerance. A randomized, double-blind, multisite placebo-controlled trial conducted in human subjects demonstrated that administration of a highly purified (>95%) short-chain galactooligosaccharide (GOS), designated “RP-G28,” significantly improved clinical outcomes for lactose digestion and tolerance. In these individuals, stool samples were collected pretreatment (day 0), after GOS treatment (day 36), and 30 d after GOS feeding stopped and consumption of dairy products was encouraged (day 66). In this study, changes in the fecal microbiome were investigated using 16S rRNA amplicon pyrosequencing and high-throughput quantitative PCR. At day 36, bifidobacterial populations were increased in 27 of 30 of GOS subjects (90%), demonstrating a bifidogenic response in vivo. Relative abundance of lactose-fermenting Bifidobacterium, Faecalibacterium, and Lactobacillus were significantly increased in response to GOS. When dairy was introduced into the diet, lactose-fermenting Roseburia species increased from day 36 to day 66. The results indicated a definitive change in the fecal microbiome of lactose-intolerant individuals, increasing the abundance of lactose-metabolizing bacteria that were responsive to dietary adaptation to GOS. This change correlated with clinical outcomes of improved lactose tolerance.